The Effects of a Multilinguistic Morphological Awareness Approach for Improving Language and Literacy. (January 2014) - Wolter, Julie A.; Dilworth, Valisa
The purpose of this study was to examine the effectiveness of a multilinguistic intervention to improve reading and spelling in primary grade students who struggle with literacy. Twenty second-grade students with spelling deficits were randomly assigned to receive a multilinguistic intervention with a phonological and orthographic awareness emphasis, or one with an additional morphological awareness focus. The morphological intervention group performed better on standardized measures of reading comprehension, and spelling, and on a nonstandardized spelling test of morphological patterns. Both groups improved and no between-group differences were found on a standardized measure of word identification and word attack, as well as on a nonstandardized spelling test of orthographic patterns.